ESTABLISHING RELATIONSHIP BETWEEN FACTORS AFFECTING BUILDING DEFECTS AND BUILDING CONDITION - Yacob, Syamilah; Ali, Azlan Shah; Au-Yong, Cheong Peng (Journal of Surveying, Construction and Property, 2019)
Defects and damage to the building are defined as the failure of the ability of the building to deliver services as expected. Inefficiency in handling defects or damage buildings systematically have to cause various effects and negative impact to users and is also the owner of the building. A total of 300 school buildings has been chosen for this study to identify the factors contribute to the building defects and to identify the condition of the buildings. The purpose of this paper is to establish the relationship between factors affecting, defects and building condition. The data is collected from through secondary reports from archive document of Public Work Department (PWD) Malaysia. A semi structure interview was conducted to confirm the common factors contribute to the defects especially for building in Malaysia. The findings show the 7 factors contribute a significant relationship with building condition of the school building such as maintenance, waterproofing, vandalism, lack of supervision, cleaning, user and the chemical agent. Result also shows found that 16 schools in good condition, 218 schools in average condition, 65 schools in critical condition and 1 school in very critical condition.